Effect of defects originating under the proton irradiation on the electrophysical and detector properties of CdTe:Cl and CdZnTe - Kondrik, A.I. (Вопросы атомной науки и техники, 2021)
The work is dedicated to studying by computer modeling the mechanisms of the influence of radiation defects, originating under high energy proton irradiation, on the resistivity ρ, lifetime of nonequilibrium electrons τₙ and holes τₚ in CdTe:Cl and Cd₀.₉Zn₀.₁Te, and charge collection efficiency η of room temperature ionizing radiation detectors based on these materials. The effect of recombination at deep levels of radiation defects on the degradation of τₙ, τₚ, and η of detectors based on CdTe:Cl and Cd₀.₉Zn₀.₁Te was studied. Energy levels of radiation defects also substantially effect on compensation degree of semiconductor decreasing ρ. The main factors affecting the abrupt or gradual decrease in the resistivity and charge collection efficiency of these detectors during their bombardment by high-energy protons, leading to complete degradation of their recording ability, were found. The important role of purity and deep donor concentration in initial state of the detector material was indicated. Методом комп’ютерного моделювання вивчено механізми впливу радіаційних дефектів, що виникають при опроміненні протонами високих енергій, на питомий опір ρ, час життя нерівноважних електронів τₙ і дірок τₚ у CdTe:Cl і Cd₀.₉Zn₀.₁Te та ефективність збору заряду η детекторів іонізуючого випромінювання на основі цих матеріалів, що працюють при кімнатній температурі. Досліджено вплив рекомбінації на глибоких рівнях радіаційних дефектів на деградацію τₙ, τₚ, і η детекторів на основі CdTe:Cl і Cd₀.₉Zn₀.₁Te. Встановлені основні фактори, якi впливають на різке або поступове зниження питомого опору та ефективності збору заряду цих детекторів при їх бомбардуванні протонами високих енергій, що призводить до повної деградації їх реєструючої здатності. Відзначено важливу роль чистоти і концентрації глибоких донорів у початковому стані неопроміненого детекторного матеріалу. Методом компьютерного моделирования изучены механизмы влияния радиационных дефектов, возникающих при облучении протонами высоких энергий, на удельное сопротивление ρ, время жизни неравновесных электронов τₙ и дырок τₚ в CdTe:Cl и Cd₀.₉Zn₀.₁Te и на эффективность сбора заряда η работающих при комнатной температуре детекторов ионизирующего излучения на основе этих материалов. Исследовано влияние рекомбинации на глубоких уровнях радиационных дефектов на деградацию τₙ, τₚ, и η детекторов на основе CdTe:Cl и Cd₀.₉Zn₀.₁Te. Установлены основные факторы, влияющие на резкое или постепенное снижение удельного сопротивления и эффективности сбора заряда этих детекторов при их бомбардировке протонами высоких энергий, приводящих к полной деградации их регистрирующей способности. Отмечена важная роль чистоты и концентрации глубоких доноров в исходном состоянии необлученного материала детектора.